﻿A new species of Metopiellus (Coleoptera, Staphylinidae, Pselaphinae) from the northern Colombian Amazon - Gianpiero Fiorentino; Maria C. Tocora; Sebastian Ramirez (ZooKeys, 2022)
The genus Metopiellus (Staphylinidae, Pselaphinae) is confirmed in Colombia with the description of Metopiellus guanano sp. nov. from the northern Amazon. Major diagnostic characters, a distributional map, and ecological data are given. Finally, a previous taxonomic key to Metopiellus is updated to include the new species.